2022
DOI: 10.1038/s41598-022-10700-3
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the gastrointestinal microenvironment during high-dose chemotherapy and stem cell transplantation by inhibiting IL-1 signaling with anakinra

Abstract: High-dose chemotherapy causes intestinal inflammation and subsequent breakdown of the mucosal barrier, permitting translocation of enteric pathogens, clinically manifesting as fever. Antibiotics are mainstay for controlling these complications, however, they are increasingly recognized for their detrimental effects, including antimicrobial resistance and dysbiosis. Here, we show that mucosal barrier injury induced by the mucotoxic chemotherapeutic agent, high-dose melphalan (HDM), is characterized by hyper-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…In an in vivo rat study, Ozcicek et al showed that the treatment of anakinra (50–100 mg/kg) restored the levels of inflammatory markers (IL‐1β, IL‐6 and TNF‐α) and reduced the morphologic GI damage induced by methotrexate (5 mg/kg) 24 . In the clinical study performed by Wardill et al in 2022, 26 patients treated with 300 mg anakinra after high‐dose melphalan (200 mg/m 2 ) avoided severe fever. They also showed in rats that the use of anakinra at a higher dose (200 mg/day for 5 days) reduced body weight loss and restored appetite and plasma citrulline, a marker used for small intestinal toxicity 45 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In an in vivo rat study, Ozcicek et al showed that the treatment of anakinra (50–100 mg/kg) restored the levels of inflammatory markers (IL‐1β, IL‐6 and TNF‐α) and reduced the morphologic GI damage induced by methotrexate (5 mg/kg) 24 . In the clinical study performed by Wardill et al in 2022, 26 patients treated with 300 mg anakinra after high‐dose melphalan (200 mg/m 2 ) avoided severe fever. They also showed in rats that the use of anakinra at a higher dose (200 mg/day for 5 days) reduced body weight loss and restored appetite and plasma citrulline, a marker used for small intestinal toxicity 45 .…”
Section: Discussionmentioning
confidence: 99%
“…While our observations for anakinra agree with corresponding data in humans, the translational potential of data generated in this rat model must be further explored. 26 For instance, the time-dependent effects, as well as the optimal dose range, dose ratio and synergistic effects of the two drugs must be elucidated. Pathogenesis of CIM involves a range of complex molecular and cellular events, such as the mucosal release of IL-1, IL-6, IL-10 and TNF-α and other relevant cytokines, and this warrants further mechanistic studies in a complex in vivo model that best mimics the clinical situation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations